Effects of Various Modified Corn Protein Inclusion Rates on Nursery Pig Growth Performance - Rafe Q. Royall; Ty H. Kim; Jason C. Woodworth; Mike D. Tokach; Joel M. DeRouchey; Jordan T. Gebhardt; Robert D. Goodband; Keith Mertz; John F. Patience (Kansas Agricultural Experiment Station Research Reports, 2023)
This experiment was conducted to determine the optimum feeding strategy of a modified corn protein product (MCP; P4000; Cargill Starches, Sweeteners, & Texturizers, Blair, NE) on growth performance and fecal dry matter of nursery pigs. A total of 360 barrows (DNA 200 × 400; initially 12.0 ± 0.14 lb) were used in a 42-d growth trial. Pigs were weaned at approximately 21 d of age, randomly allotted to pens in 1 of 2 weight blocks based on initial BW (initially 10.8 and 13.2 lb), and then allotted to 1 of 6 dietary treatments in a completely randomized design. There were 5 pigs per pen and 12 pens per treatment across 2 barns. Dietary treatments were corn-soybean meal-based and arranged in a 2 × 3 factorial with 2 levels of MCP in phase 1 (10 or 12%) and 3 inclusion rates of MCP in phase 2 (4, 6, or 8%). Treatment diets were formulated in two dietary phases and fed from d 0 to 10 and d 10 to 23, respectively, with a common phase 3 diet that did not contain any MCP fed for the remainder of the study. A tendency was observed for a 3-way interaction for weight block × phase 1 diet × phase 2 diet (P= 0.064) on d 42 BW. This interaction was a result of feeding increasing levels of MCP quadratically increasing, then decreasing, BW of lightweight pigs, regardless of phase 1 inclusion. However, in heavyweight pigs, increasing MCP in phase 2 diets quadratically decreased, then increased, BW of pigs fed 10% MCP in phase 1, while increasing MCP in phase 2 linearly decreased BW in heavyweight pigs fed 12% MCP in phase 1. Additionally, during the common period (d 23 to 42) there was a 3-way interaction (P= 0.038) for ADG, in which lightweight pigs previously fed 10 and 8% MCP (phase 1 and 2, respectively) had decreased ADG, while feeding increasing MCP in phase 2 to lightweight pigs fed 12% MCP in phase 1 quadratically increased, then decreased, common period ADG. However, for heavyweight pigs the previous MCP feeding strategies did not affect ADG during the common period. During phase 1 (d 0 to 10) pigs fed 10% MCP had greater(P= 0.032) ADFI than those fed 12% MCP, resulting in a tendency (P= 0.065) for greater ADG. Throughout the experiment (d 0 to 42) feeding 10% MCP in phase 1 tended (P= 0.077) to increase ADG. During phase 2 (d 10 to 23) feeding increasing levels of MCP quadratically improved, then worsened (P= 0.018) feed efficiency, leading to a tendency for a quadratic effect (P= 0.066) on feed efficiency throughout the treatment period. There were no 2- or 3-way interactions observed (P>0.10) on fecal dry matter. Nevertheless, pigs fed 12% MCP had greater (P= 0.024) fecal dry matter at d 10 compared to those fed 10% MCP. However, the inverse was true on d 23, in which pigs fed phase 1 diets with 10% MCP had greater (P= 0.016) fecal dry matter compared to those fed 12% MCP. In summary, feeding 10% MCP in phase 1 tended to improve BW, ADFI, and ADG compared to a 12% MCP level. Moreover, 6% MCP during phase 2 appeared to have a positive impact on feed efficiency during the treatment period but did not impact overall feed efficiency.
Keywords: corn; corn protein; growth; nursery pig